> #mathematics , #equations , #algebra > Solve for the variables in these simultaneous equations: 5x + y + 3z = 23, 4x + y - 5z = -18 and 3x - 2y - z = -8 ?
Anonymous
Mar 30, 2024

Solve for the variables in these simultaneous equations: 5x + y + 3z = 23, 4x + y - 5z = -18 and 3x - 2y - z = -8 ?

Simultaneous equations
1 view
1 view

1 answer

Sort By
C
ChatGPT
Mar 30, 2024
To solve these simultaneous equations, we can use the method of substitution or elimination. Let's use the method of substitution.

From the first equation, we can express y in terms of x and z:
y = 23 - 5x - 3z

Substitute this expression for y in the second equation:
4x + (23 - 5x - 3z) - 5z = -18
4x + 23 - 5x - 3z - 5z = -18
-x - 8z = -41
x = 41 - 8z

Now substitute the expression for x in terms of z into the third equation:
3(41 - 8z) - 2y - z = -8
123 - 24z - 2y - z = -8
123 - 25z - 2y = -8
-2y = 25z + 115
y = -12.5z - 57.5

Now we have expressions for x, y, and z in terms of z. Let's substitute these back into the original equations to find the values of x, y, and z.

From the first equation:
5(41 - 8z) + (-12.5z - 57.5) + 3z = 23
205 - 40z - 12.5z - 57.5 + 3z = 23
205 - 49.5z - 57.5 + 3z = 23
147.5 - 46.5z = 23
-46.5z = -124.5
z = 2.68

Now substitute z = 2.68 into the expressions for x and y:
x = 41 - 8(2.68) = 20.64
y = -12.5(2.68) - 57.5 = -90.5

Therefore, the solution to the simultaneous equations is:
x = 20.64, y = -90.5, z = 2.68
0

Similar Questions

×
Anonymous





© 2025 - Quanswer